Archaeosomes and Tetraether Lipid Liposome - Freisleben, Hans-Joachim (UI Scholars Hub, 2012)
Archaea have phytanyl ether lipids which is one of the characteristics that separates them from bacteria and eukaryotes. Some archaea have also unique membrane spanning tetrae ther lipids (T EL); in Sulfolobus and Ihermoplasma species these TELmake up the majority of total membrane lipids. Archaeal lipids are able to form stable liposomal structures, both from membrane factions, mainly the polar membrane fraction, i.e. archaeosomes, or from highly purified TEL (tetraether lipid liposomes). Liposomes of the main polar lipid (MPL) from thermoacidophilic archaeon Ihermoplasma acidophilum were thoroughly inevstigated. Archaeosomes and TEL liposomes exhibit extremely low proton permeability and high stability at low pH, which makes them suitable to delivery of therapeutics and vaccines via the gastro-inetestinal route. Liposomes from egg lecithin can be stabilized by incorporation of 11-12 mole% MPL. MPL liposomes show long-term shelf stability even at high temperatures without conservation. The size of MPL liposomes between 100 nm (unilamellar) and several gm (multilamellar) depends mainly on the method of preparation. Toxicity and mutagenicity have not been detected in toxicological screening. This is a review report on the lipid from archaea to be developed as an alternative to conventional liposome for various industrial applications, especially for pharmaceutical industry.